The secondary school students’ interest toward the TVET programs: demographic differences - Azeem, Nazia; Omar, Muhd Khaizer; Mat Rashid, Abdullah; Abdullah, Arnida (Society for Research and Knowledge Management, 2022)
Technical and Vocational Education and Training (TVET) has been globally recognized as one of the most vital subjects in any educational system. Pakistan is currently confronted with numerous challenges because of globalization and the emergence of new economic and social orders. To satisfy the updated requirements of economic trends, current educational systems must prioritize TVET as the most effective tool for satisfying globalization expectations. This study aimed to determine the demographic differences of secondary school students' interest toward TVET programs, which may be considered success factors for future enrollment initiatives. We perform an in-depth investigation into the relationship between students' interest in TVET programs and their demographic features, including gender, field of education, and geography. A total of 386 secondary school pupils in Pakistan participated in the study. A cross sectional research approach was employed. The mean, frequency, t-test, and ANOVA results were calculated on the collected data using the Statistical Package for the Social Sciences (SPSS). The findings indicate that students' perceptions of their interest in the TVET programs on all three dimensions (i.e. affection, cognition and conation) were somewhat poor. The t-test revealed a statistically significant difference in male and female students' interest in TVET programs. Male students were more interested in TVET programs compared to females. According to their field of education, the one-way ANOVA test revealed a substantial difference in their interest in TVET programs. Tukey HSD post-hoc analysis results suggest that there is a substantial disparity in students' interest in TVET programs in the field of education. The mean scores indicate that students in the humanities group were more interested in TVET programs, followed by bioscience, and computer science. The t-test reveals that students who live in urban regions have a higher level of interest compared to those who live in rural areas. The data gathered from this study provide insight onto the possible approaches academic institutions can take to prepare for and address current problems associated with introducing TVET programs in secondary schools. This paper argues for the need to integrate TVET programs in Pakistan which can promote transformative, lifelong learning and provide vital implications with recommendations for policy and practice.